2012
DOI: 10.1111/j.1365-3059.2012.02622.x
|View full text |Cite
|
Sign up to set email alerts
|

High throughput real‐time RT‐PCR assays for specific detection of cassava brown streak disease causal viruses, and their application to testing of planting material

Abstract: Cassava brown streak disease (CBSD) caused by Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) is causing severe losses in cassava production in Kenya, Tanzania and Uganda. Two real-time RT-PCR assays based on TaqMan chemistry capable of detecting and distinguishing these two viruses are described. These assays were used to screen 493 cassava samples collected from western and coastal Kenya, the main cassava regions of Uganda and inland Tanzania. Both viruses were found in all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 18 publications
0
61
0
Order By: Relevance
“…This indicates that presence of UCBSV does not seem to affect accumulation of CBSV RNA and implies the existence of cassava genotype‐specific resistance to infection with UCBSV. Presence of CBSV in all samples studied here shows this virus to be present at higher levels than previously reported at Namulonge (Uganda), in contrast to UCBSV (Mbanzibwa et al ., ; Winter et al ., ; Legg et al ., ; Adams et al ., ); this indicates that CBSV is replacing UCBSV as the more common pathogen at this location. Additional studies would be beneficial to determine if a similar pattern is occurring elsewhere in East Africa.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This indicates that presence of UCBSV does not seem to affect accumulation of CBSV RNA and implies the existence of cassava genotype‐specific resistance to infection with UCBSV. Presence of CBSV in all samples studied here shows this virus to be present at higher levels than previously reported at Namulonge (Uganda), in contrast to UCBSV (Mbanzibwa et al ., ; Winter et al ., ; Legg et al ., ; Adams et al ., ); this indicates that CBSV is replacing UCBSV as the more common pathogen at this location. Additional studies would be beneficial to determine if a similar pattern is occurring elsewhere in East Africa.…”
Section: Discussionmentioning
confidence: 83%
“…Variation was seen in the amount of viral RNA present in the leaf canopy with leaf age and correlated with CBSD symptom appearance (Table S2); this confirms previous reports (Moreno et al ., ; Adams et al ., ). In aerial tissues, across genotypes, the youngest symptomless leaves accumulated the lowest amount of viral RNA, senescing leaves also had low amounts, stems moderate amounts, but mature non‐senescing leaves with symptoms accumulated the highest amount of viral RNA (Table S2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sample DNA was standardized to a concentration of 4.5 ng/μl and 10 μl subjected to SYBR Green I chemistry as described by Ogwok et al (2015). Amplification was performed using the following conditions: 95 °C for 3 min, followed by 40 cycles at 95 °C for 10 s and 60 °C for 30 s. Cytochrome c oxidase (COX) (Adams et al, 2013) was used as reference gene. The primers used for this experiment are listed in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…For verification of the identity of the causal organism, leaf samples of affected plants were collected, dried, and sent to the Food and Environment Research Agency in the UK for analysis by real-time PCR, as described by Adams et al (2012). It was confirmed that the leaves were positive for UCBSV and negative for CBSV (GenBank Accession No.…”
Section: Figurementioning
confidence: 99%